Two serious ladies - Bowles, Jane (Dutton, 1984)
Two serious ladies who want to live outside of themselves, Christina Goering and Frieda Copperfield embark on separate quests of salvation. Mrs. Copperfield visits Panama with her husband, where she finds solace among the women who live and work in its brothels. Miss Goering becomes involved with various men. At the end the two women meet again, each transformed by her experience.
Keywords: amériques; approches et analyses; hétérosexisme; panama; personnes lesbiennes; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis